2021
DOI: 10.3389/fgene.2021.713446
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of QTL for Mesocotyl Length in Rice Through Combining QTL-seq and Genome-Wide Association Analysis

Abstract: Mesocotyl is a crucial organ for pushing buds out of soil, which plays a vital role in seedling emergence and establishment in direct-seeded rice. Thus, the identification of quantitative trait loci (QTL) associated with mesocotyl length (ML) could accelerate genetic improvement of rice for direct seeding cultivation. In this study, QTL sequencing (QTL-seq) applied to 12 F2 populations identified 14 QTL for ML, which were distributed on chromosomes 1, 3, 4, 5, 6, 7, and 9 based on the Δ(SNP-index) or G-value s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Different crop species have evolved diverse organs to adapt to deep-sowing stressors, including elongated mesocotyl in rice ( Oryza sativa L.) [ 10 ] and elongated coleoptile in wheat ( Triticum aestivum L.) [ 11 ] and barley ( Hordeum vulgare L.) [ 12 ]. These structures help the emergence of the shoot tips and the first internode from the embryo to the soil surface; the co-elongated mesocotyl and coleoptile in maize send the buds to the soil surface [ 13 , 14 ], where natural light represses the continued elongation of mesocotyl and coleoptile and induces leaf expansion [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different crop species have evolved diverse organs to adapt to deep-sowing stressors, including elongated mesocotyl in rice ( Oryza sativa L.) [ 10 ] and elongated coleoptile in wheat ( Triticum aestivum L.) [ 11 ] and barley ( Hordeum vulgare L.) [ 12 ]. These structures help the emergence of the shoot tips and the first internode from the embryo to the soil surface; the co-elongated mesocotyl and coleoptile in maize send the buds to the soil surface [ 13 , 14 ], where natural light represses the continued elongation of mesocotyl and coleoptile and induces leaf expansion [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutants of OsPAO5 synthesize more ethylene and produce lower amounts of H 2 O 2 , resulting in a longer mesocotyl, faster seedling emergence, and higher yield potential [ 18 ]. According to the result of GWAS from other authors, eight and five high-confidence candidate genes known to be related to mesocotyl elongation were identified on chromosomes 1(2), 3,4,6,7(2),9 and 1, 3, 5, 9, 12, respectively were involved in the biological metabolism of phytohormones, cell elongation and division [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2020) reported 16 unique loci for mesocotyl elongation through a GWAS [16]. Wang et al (2021) identified 14 QTLs for mesocotyl elongation via QTL sequencing using 12 F 2 populations, and five unique QTLs with a GWAS using two diverse panels [17]. Gothe et al (2022) also identified eight QTLs for mesocotyl elongation using a GWAS [18].…”
Section: Introductionmentioning
confidence: 99%